Genetic polymorphisms in KCNJ11 (E23K, rs5219) and SDF-1β (G801A, rs1801157) genes are associated with the risk of type 2 diabetes mellitus. Issue 3 (3rd July 2018) - Rizvi, S; Raza, ST; Mahdi, F; Singh, SP; Rajput, M; Rahman, Q
Abstract: Background: Type 2 diabetes mellitus (T2DM) is a global major health problem resulting from interaction of environmental and genetic factors, examples of the latter being KCNJ11 (coding for part of the ATP-sensitive potassium channel) and SDF - 1β (coding for chemokine CXCL12). Our case-control study was conducted to assess whether recessive, dominant or additive genotype model associations of KCNJ11 (E23K, rs5219) and SDF - 1β (G801A, rs1801157) were more strongly linked to type 2 diabetes. Subjects & Methods: Genetic polymorphism analysis was performed by polymerase chain reaction-restriction fragment length polymorphism. Alleles and genotype frequencies between 200 cases and 200 controls were determined and compared . Results: The dominant (EE v EK + KK, p = 0.022) and additive (EK v EE + KK, p = 0.021) models, but not the recessive model (KK v EE + EK, p = 0.727) of KCNJ11 were linked to diabetes. Similarly, the dominant (GG v GA + AA, p < 0.001) and additive (AG v GG + AA, p=<0.001) models, but not the recessive model (AA v AG + GG, p = 0.430) of SDF - 1β were linked to diabetes. The A allele ( p = 0.006) of SDF- 1β was protective against the risk of T2DM. Conclusion: Both dominant and additive models in both KCNJ11 (E23K, rs5219) and SDF - 1β (G801A, rs1801157) genetic polymorphisms are significantly associated with type 2 diabetes.